The Evolution of Cardiovascular Surgery in Elderly Patient: A Review of Current Options and Outcomes. (9th April 2014) - Nicolini, Francesco; Agostinelli, Andrea; Vezzani, Antonella; Manca, Tullio; Benassi, Filippo; Molardi, Alberto; Gherli, Tiziano
Abstract : Due to the increase in average life expectancy and the higher incidence of cardiovascular disease with advancing age, more elderly patients present for cardiac surgery nowadays. Advances in pre- and postoperative care have led to the possibility that an increasing number of elderly patients can be operated on safely and with a satisfactory outcome. Currently, coronary artery bypass surgery, aortic and mitral valve surgery, and major surgery of the aorta are performed in elderly patients. The data available show that most cardiac surgical procedures can be performed in elderly patients with a satisfactory outcome. Nevertheless, the risk for these patients is only acceptable in the absence of comorbidities. In particular, renal dysfunction, cerebrovascular disease, and poor clinical state are associated with a worse outcome in elderly patients. Careful patient selection, flawless surgery, meticulous hemostasis, perfect anesthesia, and adequate myocardial protection are basic requirements for the success of cardiac surgery in elderly patients. The care of elderly cardiac surgical patients can be improved only through the strict collaboration of geriatricians, anesthesiologists, cardiologists, and cardiac surgeons, in order to obtain a tailored treatment for each individual patient.